KEEFEKTIFAN KOMUNIKASI KELOMPOK TANI DALAM PENERAPAN PROGRAM JARWOBANGPLUS DI KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Aprilina S, Delia; Nurmayasari, Indah; K Rangga, Kordiyana (Lampung University, 2017)
This study aims to analyze factors related to group communication effectiveness on Jarwobangplus Program implementation and to find out the relationship between the group communication effectiveness and the implementation of Jarwobangplus Program in Gadingrejo Subdistrict, Pringsewu Regency. The location of this study was chosen purposively in Gadingrejo Subdistric, Pringsewu Regency and respondents were 86 of rice farmers committed to Jarwobangplus program. Data of this research was collected on April-May 2016. The research employed survey method using descriptive analysis and used nonparametric statistic test correlation Rank Spearman to test the hypothesis. The results showed that the factors that related to group communication effectiveness are group cohesion level, leadership type and semantics disruption frequency. There was a significant correlation between the group communication effectiveness and the Jarwobangplus Program implementation in Gadingrejo Subdistrict, Pringsewu Regency with rs score of 0.233. It means that Jarwobangplus Program implementation achievement was determined by group communication effectiveness as much as 23.3 percent. Key words: group communication effectiveness, Jarwobangplus Program